Hubungan Pemenuhan Nutrisi Pada Bayi Dengan Kualitas Tidur Di BPS Ny. Siti Naimah AMd.Keb Desa Padangasri Kecamatan Jatirejo Kabupaten Mojokerto - Cainis Risqiyah Fasyah , Nurul Hidayah (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2013)
Nutristion meet a demand to baby at the age of 6-9 month can ifluence his quality of sleep. If his nutrition meet a demand is enough, it will not experience the intrude on sleep. This study uses crossectional approach. As the variables independent is nutrition meet a demand to baby at the age of 6-9 month and the quality of sleep as the variables dependent. It‟s population is baby at the age of 6-9 month. In the BPS Ny. Siti Naimah, Amd. Keb, Padangasri village – Jatirejo, Mojokerto regency as many as 49 baby. The samples were selected using total sampling as many as 39 baby. Colecting data using interview for nutrition meet a demand and quality of sleep. The data have been using the pearson chi squre. The results of this study showed baby at the age of 6- month have experienced the nutrition meet a demand is less as many as 18 baby (46,2%), and experience the intrude on sleep as many as 15 baby (38,5%). In addition to that, for the baby have nutrition meet a demand is more as many as 9 baby (23,1%), all of the baby experienced the intrude on sleep. Then, the baby have enough of nutrition meet a demand as many as 12 baby (30,8%), until that is get the intrude on sleep as many as 11 baby (28,2%). Result test of pearson chi squre using SPSS 17 can got the value PValue Cremer‟s V =0,0000, then value PValue < α (0,05). Until can to conclude H1 is accepted it means there is a relationship between meet a demand of nutrition with quality of sleep on baby at the age of 6- 9 month. The meet a demand of nutrition is less or more can influence baby sleep quality. Therefore, recomended to the health workers exspesially for midwife to provide counseling to parents of baby about the precise meet a demand of nutrition intake all at once with the visiting home for look at result of counseling gived.